AKIBAT HUKUM PELANGGARAN MEREK TERKENAL PRADA PADA PRODUK FASHION DI INDONESIA - Bernadetta Ides Bidhari, Etty Susilowati*, Hendro Saptono (Diponegoro Law Journal, 2013)
Brand is the symbol in the form of pictures, names, words, letters, numbers, color composition, or the combination of those elements having distinguishing features and used in the commercial activities of goods and services. Then, famous brand is the trade mark commonly recognized and used to the traded goods by someone or institution, both in Indonesia and other countries. Brand is closely related to unfair business competition in the form of famous brand violation, which is the imitation of famous brand.This legal research was conducted with the aims to recognize the legal causes of the violation against Prada famous brand in fashion products in Indonesia in which the brand registration is misused to imitate the existing famous brand. This research was conducted by adjusting the case occurred with the existing laws in the Act No. 15, 2001 on Brand referring to the decision of Judicial Review on the Dispute of Prada Brand. Based on the research results, it is found that the legal causes of the violation against Prada famous brand in fashion products in Indonesia (the Commercial Court Decision in Central Jakarta No. 200/Pdt.G/1998/PN.Jkt.Pst. and the Judicial Review Decision No. 274 PK/Pdt/2003) are that the legal protection for the fashion products committing brand violation against Prada brand is over after the Judicial Review Decision and the ownership returns to the original owner of Prada brand.